Pengembangan Sumber Daya Manusia Pada Masyarakat Pesisir Pantai Di Kabupaten Kepulauan Sangihe - HUMUNE, JESSICA PRISCA; Rumapea, Patar; Palar, Novie (Sam Ratulangi University, 2017)
Abstract : This study aims to determine the development of human resources in coastal communities in the sub-district tabukan sangihe archipelago. This research uses descriptive method of qualitative approach by describing data obtained from the results of research on human resource development in coastal communities. The subject of this research is the coastal community leaders who work as fishermen in three villages namely Talengen village, bungalawang village, and sensing village. In qualitative research, data collection is done by observation, interview, and documentation, and conclusion/verification. Development of human resources in coastal communities in Kecamatan Tabukan Tengah Sangihe archipelago. For now is not good because seen from the level of education, knowledge, and skills far from expected and lack of counseling or training for coastal cummunities, especially fishermen in providing knowledge about fisheries and marine and ways of cultivating marine biota. Then some things that can be suggested is to the government for coastal cummunities should be more attention, provide briefing ways to cultivate fish, provide a uniform training so that people can develop knowledge and skills received through training.Keywords Human Resource Development, Coastal Cummunities